Sensory analysis of pancakes made with sorghum flour, xanthan gum and microbial transglutaminase enzyme - Figueroa, Juan; Sánchez-Toledano, Blanca; Zegbe, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Sorghum is a cereal used as fodder, mainly. Despite being a beneficial product for human health, its consumption is little or null in Mexico. The food industry could be an alternative to diversify this cereal in products compatible with celiac people. The study was focused on the consumer’s characterization and the sensory assessment of pancakes elaborated with various proportions of xanthan gum (GX) and the microbial transglutaminase (MTG) enzyme in two cities from the central and northeastern regions of Mexico. A survey, designed and validated previously, was given to 58 consumers where the demographic characteristics of participants and the sensory analysis of nine pancakes (P) were explored. The latter were prepared with the following proportions of GX/MTG: P1 (0/0 %), P2 (0/0.25 %), P3 (0/0.5 %), P4 (0.25/0 %), P5 (0.25/0.25 %), P6 (0.25/0.5 %), P7 (0.5/0 %), P8 (0.5/0.25 %), P9 (0.5/0.5 %) and a commercial pancake (control). The study revealed that the majority of the participants were women (77.5 %). The predominant age was between 20 and 29 years (51.7 %) with a university academic level (30.2 %) and postgraduate degree (38 %), and income ≥ 20,000 MXN (53.6 %). The most preferred and accepted pancakes were P9 and P7 followed by the control, P5 and P8. However, the most accepted pancake was the control followed by P7 and P9. It is concluded that sorghum pancakes represent an alternative with health benefits for people with celiac disease.